Prevalence, Serotyping, Molecular Typing, and Antimicrobial Resistance of Salmonella Isolated From Conventional and Organic Retail Ground Poultry - Gad, Ahmed H.; Abo-Shama, Usama H.; Harclerode, Katherine K.; Fakhr, Mohamed K. (Frontiers in Microbiology, 2018)
Ground poultry is marketed as a healthier alternative to ground beef despite the fact that poultry is a major source of foodborne Salmonella. The objectives of this study were to determine the prevalence of Salmonella in Oklahoma retail ground poultry and to characterize representative isolates by serotyping, antimicrobial resistance, PFGE patterns, and large plasmid profiling. A total of 199 retail ground poultry samples (150 ground turkey and 49 ground chicken) were investigated. The overall prevalence of Salmonella in ground poultry was 41% (82/199), and the incidence in conventional samples (47%, 66/141) was higher than in organic samples (27%, 16/58). The prevalence of Salmonella in organic ground chicken and organic ground turkey was 33% (3/9) and 26% (13/49), respectively. Twenty six Salmonella isolates (19 conventional and 7 organic) were chosen for further characterization. The following six serotypes and number of isolates per serotype were identified as follows: Tennessee, 8; Saintpaul, 4; Senftenberg, 4; Anatum, 4 (one was Anatum_var._15+); Ouakam, 3; and Enteritidis, 3. Resistance to 16 tested antimicrobials was as follows: gentamycin, 100% (26/26); ceftiofur, 100% (26/26); amoxicillin/clavulanic acid, 96% (25/26); streptomycin, 92% (24/26); kanamycin, 88% (23/26); ampicillin, 85% (22/26); cephalothin, 81% (21/26); tetracycline, 35% (9/26); sulfisoxazole, 27% (7/26); nalidixic acid, 15% (4/26); and cefoxitin, 15% (4/26). All isolates were susceptible to amikacin, chloramphenicol, ceftriaxone, and trimethoprim/sulfamethoxazole. All screened isolates were multidrug resistant (MDR) and showed resistance to 4 - 10 antimicrobials; isolates from organic sources showed resistance to 5 - 7 antimicrobials. PFGE was successful in clustering the Salmonella isolates into distinct clusters that each represented one serotype. PFGE was also used to investigate the presence of large plasmids using S1 nuclease digestion. A total of 8/26 (31%) Salmonella isolates contained a ~100 Kb plasmid that was present in all Anatum and Ouakam isolates. In conclusion, the presence of multidrug resistant Salmonella with various serotypes, PFGE profiles, and large plasmids in ground poultry stresses the importance of seeking novel interventions to reduce the risk of this foodborne pathogen. Multidrug resistance is considered a high additional risk and continued surveillance at the retail level could minimize the risk for the consumer.